5-HT1A receptor ligands and their therapeutic applications: review of new patents. (2nd September 2018) - Staroń, Jakub; Bugno, Ryszard; Hogendorf, Adam S.; Bojarski, Andrzej J.
ABSTRACT: Introduction : 5-HT1A R was one of the first discovered serotonin receptors and is one of the most thoroughly studied. Dysfunctions associated with 5-HT1A R neurotransmission are linked to several psychiatric disorders, including anxiety, depression, and movement disorders. Areas covered : The current review covers patent literature published between January 2012 and May 2018. Queries were performed on Espacenet, SciFinder, clinicaltrials.gov, pharmacodia.com, and the websites of pharmaceutical companies. Expert opinion : Several novel therapeutic applications have been proposed for 5-HT1A R ligands, i.e. prostate cancer treatment, gastrointestinal and cardiopulmonary disorders, facilitation of urination and defecation, and L-DOPA-induced dyskinesia. Interestingly, no patent application has been filed by big pharma companies, while numerous researches are being conducted in smaller companies and academia.